The Catholic School According to the Code of Canon Law - Grocholewski, Zenon (Catholic Education: A Journal of Inquiry and Practice, 2008)
For close to three decades, his Eminence Zenon Cardinal Grocholeski, worked at the Supreme Tribunal of the Apostolic Signatura as notary, chancellor, secretary and prefect. A professor, scholar, and canonist of exceptional ability, he is considered one of the world’s most prominent experts on the Code of Canon Law. In light of his competence and experience, The Servant of God Pope John Paul II, appointed his Eminence as Prefect of the Dicastery for Catholic Education in 1999. This rare combination and manifestation of intellect, expertise, and dedication is witnessed in the oration presented for publication, The Catholic School According to the Code of Canon Law delivered by His Eminence, as Prefect of the Congregation of Catholic Education on May 28, 2008 at Fordham University, New York. [Introduction by Gerald M. Cattaro, professor and executive director of the Catholic School Leadership program at Fordham University, Graduate School of Education]